Occupational exposure to fungi and mycotoxins in cork industry: an exploratory study - Viegas, Susana (2017)
Cork oak is the second most dominant forest species in Portugal and makes this country the work leader in cork export. This type of industry has already been associated with occupational exposure to several fungal species, most commonly with Penicillium globrum (belonging to Penicillium section Aspergilloides) and Chrysonilia sitophila. However, occupational exposure to mycotoxins has never been studied. Here we describe an exploratory work developed in a cork industry located in Portugal aiming at assessing exposure to fungi and mycotoxins.